Investimento público no Brasil e o programa de aceleração do crescimento - Pontes, Denio Igor Silva de (2009)
This paper makes a historical survey about the investments in gross fixed capital formation and shows the evolution of the investment rates in Brazil recently. Infrastructure investments are justified by the economic growth that they stimulate. The fiscal crisis in Brazil, in the last decades, became impracticable the execution of the necessary investments to endow the country of the economical infrastructure suitable. In this scenario, the Program of Acceleration of Growth (PAC) was begun with the intention of expand and modernize the economical infrastructure available in the country. In fact, the Gross Domestic Product is growing in the last years, but the investment rates of the economy didn’t show a considerable growth when it is compared with earlier periods. In the historical series of the investment rate, Lula’s first mandate has the worst fulfillment, but it’s observed that this tendency has an inflection from the first year of the second mandate.